Engaging Youth through Community-Driven Development Objectives : Experiences, Findings, and Opportunities - Adam, Sarah G.; Kaori Oshima (World Bank Group, Washington, DC, 2014)
Community-driven development (CDD) is an approach emphasizing local control over planning and an investment resource offers important advantages for engaging young people. The World Bank's portfolio of CDD projects provides a rich repository of experiences of how this approach is being adapted to enhance the inclusion of young people. This paper synthesizes the findings of a global stocktaking on CDD and youth. The study draws from a universe of over 60 active, planned, or recently closed CDD youth projects across all regions in which the Bank operates. Significant diversity exists among these projects in terms of the extent of youth focus; size, scale, and scope; contexts and conditions to which they respond; and objectives and desired outcomes. Youth engagement is examined through three interlinked dimensions of youth development: (1) endowments or the accumulation of human capital assets; (2) employment and economic opportunities; and (3) empowerment, encompassing the concepts of participation, voice, and agency. The framework links each dimension to a domain of inclusion services, markets, and spaces within which individuals and groups take part in society. The stocktake reveals that CDD projects are contributing in significant and innovative ways to the youth development agenda in all three spheres, and offers reflections and opportunities for each dimension.